Effects of Prototype Medium on User Feedback in Product Evaluation - Bennett, Andrew. (2017)
Abstract: Understanding User feedback on design concepts can help designers tailor their process more to successfully fulfill user needs and save time and money in the product development process. This paper explores how users understand and evaluate physical prototypes and rendered prototypes of archetypal products across several measures of design quality. Sixteen participants evaluated four products represented with rendered and physical prototypes. It was found that physical prototypes were considered significantly (p; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Daniel Hannon.; Committee: Chris Rogers, and Josh Wiesman.; Keywords: Design, and Mechanical engineering.